Are Australia's Current Account Deficits Excessive? - McDermott, C. (IMF Working Papers; Working Paper ;, 1996)
This paper compares the evolution of the Australian current account balance over the period 1954-94 against an optimal current account derived from a consumption-smoothing model. The findings indicate that the Australian current account was not used to smooth consumption optimally in the period prior to the relaxation of capital controls in the early 1980s. The results also suggest that in the period since the mid-1980s Australia's current account deficits have become excessive, and that the increase in national saving required to satisfy its external borrowing constraint is about 2 to 4 percent of GDP.